2020
DOI: 10.1039/c9qm00699k
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and reversible thermochromic supramolecular polymer hydrogel and its application in protected quick response codes

Abstract: A rapid and reversible thermochromic fluorescent supramolecular polymer hydrogel prepared by orthogonal self-assembly of host–guest and metal coordination interactions, has been used in protected quick response codes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…After cooling, the gel recovered due to the reconstrcution of host‐guest interactions. [ 25,33,43 ] Besides, upon addition of KPF 6 , the gel turned into solution because the 21C7 tended to form complex with K + , resulting in the destruction of host‐guest recognition between 21C7 and secondary ammonium salt. The successive addition of 18‐crown‐6 (18C6), which exhibited higher affinity toward K + , made the gel restored.…”
Section: Resultsmentioning
confidence: 99%
“…After cooling, the gel recovered due to the reconstrcution of host‐guest interactions. [ 25,33,43 ] Besides, upon addition of KPF 6 , the gel turned into solution because the 21C7 tended to form complex with K + , resulting in the destruction of host‐guest recognition between 21C7 and secondary ammonium salt. The successive addition of 18‐crown‐6 (18C6), which exhibited higher affinity toward K + , made the gel restored.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and characterization of the requisite AIEgens, which have precedence in the literature, [ 51,52 ] are detailed in the Supporting Information (Figures S1 and S2, Supporting Information). The AIE hydrogels [ 53–55 ] were prepared by mixing PVA with AIE dots in water [ 43–45 ] (Figure S3, Supporting Information), proved through various characterization methods, including rheology, SEM, tensile experiments, and fluorescence spectroscopy. Rheological experiments shown that within a certain frequency range (0.1–100 rad s −1 at a strain of 1%), the storage modulus ( G ′) of the three hydrogels was greater than the loss modulus ( G ″), and was independent of frequency (Figure S4, Supporting Information), indicating the formation of a gel state.…”
Section: Construction Of the Information Code By Interfacial Supramolecular Adhesion Of Different Aie Hydrogelsmentioning
confidence: 99%
“…(A) Schematic illustration showing the fabrication of AIE‐active FPH via Host–guest interactions, as well as the cartoon showing the protected quick response (QR) codes with improved durability and security. Reproduced with permission: 2020, The Royal Society of Chemistry [ 52 ] …”
Section: Aggregation‐induced Emissive Polymeric Hydrogels Based On Organic Aiegensmentioning
confidence: 99%